1996
DOI: 10.1007/bf02883398
|View full text |Cite
|
Sign up to set email alerts
|

The effects of caffeine on blood pressure and heart rate: A review

Abstract: Concerns have been raised frequently about caffeine's potential for increasing blood pressure (BP) and posing a risk for cardiovascular disease. This review surveys research concerning the effects of caffeine on BP and heart rate (HR). Tolerance to caffeine, family history of hypertension, borderline hypertension, and hypertension are also examined as potential moderators. Results from epidemiological studies are inconsistent. Experimental laboratory studies have generally found that caffeine produces acute ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 92 publications
6
29
0
2
Order By: Relevance
“…The observed autonomic and respiratory response patterns were in accordance with previous evidence from studies with anxiety-unselected populations (Flaten and Blumenthal 1999;Green et al 1996;Mikalsen et al 2001;Sawyer et al 1982). As reported earlier, Pané-Farré et al (2014) revealed an exaggerated respiratory response to unexpected caffeine administration in high compared to low anxiety sensitive persons who were classified as non-habitual caffeine users.…”
Section: Autonomic and Respiratory Responsessupporting
confidence: 92%
“…The observed autonomic and respiratory response patterns were in accordance with previous evidence from studies with anxiety-unselected populations (Flaten and Blumenthal 1999;Green et al 1996;Mikalsen et al 2001;Sawyer et al 1982). As reported earlier, Pané-Farré et al (2014) revealed an exaggerated respiratory response to unexpected caffeine administration in high compared to low anxiety sensitive persons who were classified as non-habitual caffeine users.…”
Section: Autonomic and Respiratory Responsessupporting
confidence: 92%
“…The small sample size (n=5) of this study's ECG findings supports other investigations which show a transient reduction in heart rate and increase in blood pressure at high caffeine doses (>150 mg/person) [16][17][18]. Interestingly, other studies do not elicit this cardiovascular response at lower doses of caffeine [6,10].…”
Section: Discussionsupporting
confidence: 84%
“…Nevertheless, we consider these to be distinct aspects of recovery, worthy of study in their own right~Earle, Linden, & Weinberg, 1999;Linden et al, 1997!. Finally, there is some indication that the 2-hr interval of caffeine abstinence required of participants may have been insufficient to rule out potential cardioactive effects~e.g., Green, Kirby, & Suls, 1996!. The present findings may offer insight into the roles of different hemodynamic response patterns in the pathogenesis of essential hypertension. The prolonged delay in CO and TPR speech recovery exhibited by vascular responders is consistent with classic stress model conceptualizations of a maladaptive stress-responsẽ e.g., Dienstbier, 1989;McEwen, 1998;Selye, 1978!, whereas the rapid recovery displayed by the myocardial group could be viewed as adaptive.…”
Section: Discussionmentioning
confidence: 93%